Binder-free 2D titanium carbide (MXene)/carbon nanotube composites for high-performance lithium-ion capacitors. Issue 13 (14th March 2018) - Yu, Peng; Cao, Gejin; Yi, Sha; Zhang, Xiong; Li, Chen; Sun, Xianzhong; Wang, Kai; Ma, Yanwei
Abstract : A full-cell lithium-ion capacitor is assembled using a Ti3 C2 T x /CNT film as the anode and activated carbon as the cathode. Abstract : Two-dimensional (2D) MXenes have a very good application prospect in the field of electrochemical energy storage due to their metallic conductivity, high volumetric capacity, mechanical and thermal stability. Herein, we report the preparation of titanium carbide (Ti3 C2 T x )/carbon nanotube (CNT) flexible self-supporting composite films by vacuum filtration. The CNTs can effectively prevent Ti3 C2 T x from stacking and improve the electrochemical performance. The as-fabricated Ti3 C2 T x /CNT film shows a high reversible capacity of 489 mA h g −1 at a current density of 50 mA g −1 together with good cycling performance. The full-cell lithium-ion capacitor (LIC) is assembled using the Ti3 C2 T x /CNT film as the anode and activated carbon as the cathode. The LIC exhibits a high energy density of 67 Wh kg −1 (based on the total weight of the anode and the cathode), and a good capacity retention of 81.3% after 5000 cycles. These results suggest that Ti3 C2 T x -CNT films are promising as anode materials for lithium ion capacitors.